Paradigma Ergo-Ikonik: Merekayasa Nilai melalui Kecerdasan, Estetika, dan Keberpusatan pada Manusia - Andriyansah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
In the era of intelligence-driven business, conventional definitions of value creation, predominantly anchored in cost efficiency and process speed, are increasingly insufficient. While data analytics and artificial intelligence (AI) have optimized the functional dimensions of e-business, a gap remains in understanding how data can be transformed into profound symbolic value. This paper introduces the “Ergo-Iconic Paradigm,” a novel theoretical framework that redefines digital value as the synthesis of the ergo dimension—utility, usability, and frictionless interaction—and the iconic dimension—symbolic identity, aesthetic distinction, and emotional resonance. Drawing on recent developments in business intelligence and consumer behavior analysis, this paper argues that the highest form of data transformation lies in creating products and services that are simultaneously seamless in function and powerful in identity. Using a systematic literature review and conceptual framework development methodology, this study integrates Andriyansah’s foundational work on ergo-iconic value with contemporary findings on AI-driven personalization, business model innovation, and supply chain resilience. The findings propose a new metric for value engineering, suggesting that sustainable competitive advantage in the post-digital economy depends on the algorithmic balance between ergonomic fit and iconic appeal. This paradigm shifts the discourse from mere data processing to the engineering of meaningful digital experiences. The paper presents theoretical foundations grounded in the Resource-Based View, Service-Dominant Logic, and Value Co-creation Theory, alongside practical implications for managers seeking to leverage AI for both operational excellence and brand differentiation.